Learning Media Development Training for Teachers of SD Negeri Baun 1 - Martin Chrisani Liufeto; I Made Suardana; Koroh, Tince Dormalin; Norianti Pai Tiba; Jeheskiel Saudale; Revianti Hithaubesi (Amalee: Indonesian Journal of Community Research and Engagement, 2025)
The learning media available at SD Negeri Baun 1 already exist, but are not enough to attract students' motivation, attention, and enthusiasm in learning. The purpose of this community service activity is to find out the basic techniques of creative and innovative learning and develop them. The community service method used in this PKM activity is Community-Based Research (CBR). The technique in this activity is training, where teachers are trained to create learning media that support learning activities. The results of this PKM activity show that the activity results are measured based on participant satisfaction in participating in the activity, namely 80% very useful, 20% useful, 0% less useful, and 0% not useful. This PKM activity concludes that the school is very satisfied with the activities carried out by the community service team because it provides considerable benefits, namely increasing knowledge about the application of Padlet, Tarsiamaker, Puzzlemaker, Wordwall, and Genially learning media